EDUKASI PENCEGAHAN COVID 19 BAGI PENERIMA PROGRAM BANSOS DI DESA LONGOS KABUPATEN SUMENEP - Enza Resdiana; Irma Irawati P.; Nur Inna Alfiyah (Dharma: Jurnal Pengabdian Masyarakat, 2020)
The rapid spread of Covid-19 has caused the government to adopt a “at home” policy by stopping various economic activities in the community. Health protocols that are carried out are maintaining distance, avoiding crowds, using masks, washing hands. As a form of implementation of Government policies, community empowerment is needed to minimize the number of Covid-19 cases, this empowerment is specifically aimed at rural communities with an interest in Social Assistance Recipients, given that the poor have low awareness of the importance of keeping free from exposure to Covid-19. . Therefore, empowerment will be carried out in the form of providing information and inviting social assistance recipients to live healthy lives and avoid exposure to Covid-19. The method of implementing activities in community service is by providing education which is carried out involving the recipient community of social assistance and interactive communication. The results of the implementation of community service activity programs in the form of providing covid-19 prevention education for social assistance recipients in Longos Village received enthusiasm and a positive response even though basically the community service team was only trying to provide additional insight for the community related to covid-19, how to avoid and prevent and change habits to be healthier by observing health protocols.